FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERKULOSIS PARU PADA USIA PRODUKTIF DI PUSKESMAS KECAMATAN PASAR MINGGU TAHUN 2021 - Aldila Nur Rahmawati; Gisely Vionalita; Intan Silviana Mustikawati; Rini Handayani (Jurnal Kesehatan Masyarakat, 2022)
Tuberculosis (TB) is a major global health problem with an estimated 10.4 million new TB cases worldwide. Based on data from health reports at the Pasar Minggu Subdistrict Health Center in 2021 (January - August) there were 82 new cases of bacteriological confirmation (18.5%) from 441 patient visits. The purpose of this study was to determine the factors related to the incidence of pulmonary tuberculosis at the Pasar Minggu Subdistrict Health Center in 2021. This study used a cross sectional design with the population being all medical records of patients at the Pasar Minggu subdistrict health center as many as 441 medical records and samples taken used as many as 117 medical records. Data analysis used univariate and bivariate analysis with Chi Square test. The results of univariate analysis showed that more patients had tuberculosis, age at risk, male sex, highly educated, working, good nutritional status. The results of the bivariate analysis showed that there was a relationship between age, gender, nutritional status and the incidence of tuberculosis. It is recommended that the Puskesmas Puskesmas run and socialize the program to increase community independence so that the community, especially those at the age who are not at risk (over 50 years), implement a smoking cessation clinic program (KBM). carry out a nutritional counseling program specifically for tuberculosis patients who experience poor nutritional status and carry out a program of providing additional food for tuberculosis patients who cannot afford it in the form of packaged milk, eggs and biscuits during the treatment of pulmonary tuberculosis.Keywords: Tuberculosis, Age, Gender, Nutritional Status.